Effectiveness of Mucoadhesive Patch Clitoria Ternatea Extract in Wound Healing Process After Tooth Extraction in Sprague Dawley Rats - Amalia, Rahma Ika; Prastiya, Wahyu; Meirawati, Nur; Hirawan, Helmi; Sari, Dwi Nur Indah (Journal of Dentistry Indonesia, 2024)
Objective: This study aims to evaluate the effectiveness of mucoadhesive patch clitoria ternatea extract for wound healing post-tooth extraction. Methods: The research was carried out experimentally in a laboratory. 30 Sprague Dawley rats were selected and randomly divided into mucoadhesive patch clitoria ternatea (MPCT) 5%, 10%, 15%, positive and negative control groups. The upper incisors of rats were extracted and treated once a day for 7 and 14 days. Wound healing was observed based on histological observation (fibroblasts, collagen density, and epithelial thickness). Data was analyzed statistically. Results: MPCT 15% applied for 14 days showed the highest number of fibroblasts, collagen density, and epithelial thickness among all groups and was significantly different compared to the positive control and negative control (p < 0.05). Conclusion: Mucoadhesive patch clitoria ternatea extract was effective in the wound healing process after tooth extraction, with the most effective concentration is 15%.